Thyroid dysfunction in a UK hepatitis C population treated with interferon-α and ribavirin combination therapy - Costelloe, Seán J.; Wassef, Nancy; Schulz, Josephine; Vaghijiani, Tina; Morris, Catherine; Whiting, Stephen; Thomas, Michael; Dusheiko, Geoffrey; Jacobs, Michael; Vanderpump, Mark P. J. (Clinical endocrinology (Oxford), 2010)
Summary Objective  To assess the incidence of thyroid dysfunction (TD) in a UK cohort of patients with hepatitis C virus (HCV) infection treated with interferon‐α (IFNα) and ribavirin combination therapy (IFN/RBV). Design, patients and measurements  A retrospective study of 288 patients who received IFN/RBV for HCV during a 2‐year period from January 2006 was performed. Thyroid function was assessed during a 24‐week or 48‐week course of IFN/RBV. If serum thyrotrophin (TSH) became undetectable (<0.01 mU/l) and serum free thyroxine (T4) was raised, a diagnostic thyroid isotope scan was performed. Results  Full medical records were examined for 260 patients (172 men, 88 women) included in the study, of whom 22.3% (16.9% of men, 33.0% of women) developed TD during IFN/RBV. In total, 10.4% developed a suppressed serum TSH (0.8% Graves’ disease, 9.6% transient thyroiditis) while 11.9% developed an elevated serum TSH with 1.5% becoming permanently hypothyroid and requiring levothyroxine therapy. Women had a relative risk (RR) for developing TD of 1.96 (CI: 1.75–3.03, P = 0.004). A serum TSH ≥1.75 mU/l and a positive thyroid peroxidase (TPO) antibody titre pretherapy were associated with RRs for progression to TD of 6.02 (CI: 2.95–12.78, P < 0.0001) and 4.35 (CI: 2.58–6.52; P < 0.0001), respectively, while combination of baseline TSH and TPO antibody data predicted progression to TD with a sensitivity of 94.7%. Conclusions  Although TD was common in this cohort, just 2.3% developed TD that required ongoing therapy. Pre‐IFN/RBV serum TSH and TPO antibody titre were found to predict progression to TD in this group of patients.